2011
DOI: 10.1002/ejoc.201100606
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Rotors as Fluorescent Viscosity Sensors: Molecular Design, Polarity Sensitivity, Dipole Moments Changes, Screening Solvents, and Deactivation Channel of the Excited States

Abstract: A library of new fluorescent molecular rotors (FMRs) for viscosity sensing was synthesized. The sensitivity of the fluorescence emission toward solvent viscosity and polarity was investigated by using UV/Vis absorption, fluorescence emission spectra, and theoretical calculations. For the new FMRs, red-shifted emissions at 620 nm, Stokes shifts of 170 nm, and up to 40-fold fluorescence enhancement upon increasing the viscosity of solvents were observed (cf. known FMRs with emissions at 491 nm, Stokes shift of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(31 citation statements)
references
References 56 publications
(140 reference statements)
0
31
0
Order By: Relevance
“…[26][27][28] FMRs have become rather popular in the last 5-10 years thanks to their easy applicability as non-mechanical viscosity sensors, tools for protein characterization, and local microviscosity imaging. [29][30][31][32][33][34][35][36][37] Remarkably, their sensitivity towards viscosity and viscosity changes has reached a precision comparable to that of commercial mechanical rheometers with shorter measurement time.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] FMRs have become rather popular in the last 5-10 years thanks to their easy applicability as non-mechanical viscosity sensors, tools for protein characterization, and local microviscosity imaging. [29][30][31][32][33][34][35][36][37] Remarkably, their sensitivity towards viscosity and viscosity changes has reached a precision comparable to that of commercial mechanical rheometers with shorter measurement time.…”
Section: Introductionmentioning
confidence: 99%
“…where h is the viscosity of the medium in which the molecular rotors are present, a is a constant, and x is the viscosity sensitivity of the molecular rotor [11]. Therefore, for a molecular rotor, the dependence of the fluorescence intensity upon molecular absorption and viscosity should be expressed as:…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we showed that the acetylene bond can be used to extend the absorption/emission wavelengths of the rotors. [21] However, we found that the sensitivity of the resulting rotors to viscosity was reduced. Thus, we set out to explore another strategy to improve the photophysical properties of the rotors.…”
Section: Design Of the Fluorescent Molecular Rotorsmentioning
confidence: 94%